Formulation improvement, process development, and quality assessment of chili shrimp paste - Sobhi, Babak (2012)
Chili shrimp paste (CSP), also known as sambal belacan in Malaysia, is wellliked in many Southeast Asian countries and is recognized as a national heritage food by the Malaysian Ministry of Cultural Arts and Heritage. This savory condiment is prepared by pounding fresh chilies with a small amount of fermented shrimp paste in stone mortar. No standard formulation or safety regulations have yet been developed for this product which could be used as a reference in food industries. It is usually prepared fresh, just before serving due to its perishable nature. In addition, pounding the chili in mortar to get the desired texture is a tiring job. This study was conducted to improve formulation, assess quality and develop processing methods for CSP. Results indicated that a typical product preferred by panelists contains approximately 70% moisture content, 27°Brix, 4.4% total salt content, 10% sucrose content, thick and chunky paste withlightness value (L) of 23, redness value (a) of more than 20 and yellowness value (b) of 12. The instrumental methods developed included texture analysis using the back extrusion (sphere and cylinder) and the rheometer using an oscillation frequency sweep (vane in large cup) were found suitable to evaluate textural and rheological quality of CSP. Pastes prepared using an electrical stone mill with parallel plates (120 μm gap) had textural and rheological characteristics similar to the traditionally prepared products. Samples with acceptable textural properties were tested for its rheological behavior in the temperature range of 25-85 °C. Shear stress-shear rate data were adequately fitted to rheological models, i.e. Power law, Bingham plastic, Herschel-Bulkley, Casson and Mizrahi and Berk models, with the Casson being the most fitted (R2 = 0.981) model. The tested paste showed non-Newtonian shear thinning behavior as the flow behavior index was less than one. Experimental yield stress values were different from those calculated using models, thus it is more accurate to determine yield stress from experiments. The defined flow behavior of CSP will allow engineers to design industrial process equipment. Thermal process (80 °C, 21.6 min) was effective and reliable in controlling microorganisms and deactivate the peroxidase as a deteriorative enzyme. In contrast, physicochemical and sensorial properties of CSP were negatively affected by heating. Electron beam irradiation (10 kGy) as an alternative non-thermal processing method was able to effectively control the microorganisms in CSP. Despite insignificant reduction in peroxidase activity and destructive effect on texture, irradiation was a better tool compared to thermal treatment in preserving phenolics, capsaicinoids, color and flavor of CSP. Inconclusion, this study provided improved formulation and quality control method for textural anlysis of CSP. In addition,preliminary data for scaling up of CSP in commercial setup was obtained. Irradiation was a better processing method than thermal processing for preserving the quality of the product. Findings of this research will help future industrial implementation of commercialized CSP to meet consumer demands.